Efektivitas Kombinasi Ecoenzim dan Fitoremediasi dalam Pengolahan Limbah Praktikum Uji Asam Basa - Khoiriyani, Very; Rihhadatul Aisya, Zulfiana; Afifa, Nikmatul; Alfi Raida, Sulasfiana (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study aims to evaluate the effectiveness of the combination of ecoenzyme and phytoremediation using water hyacinth (Eichhornia crassipes) in the treatment of acid-base test laboratory waste containing vinegar and baking soda. The research method involved five treatments with variations in waste volume and the addition of ecoenzyme, as well as observations of the Total Dissolved Solids (TDS) and pH parameters for five days. The results of the observations showed that phytoremediation alone (Treatments 1 and 2) was able to reduce TDS, but the addition of ecoenzyme significantly increased the efficiency of TDS reduction. Treatment 3 (600 ml of waste = 50 ml of ecoenzyme + water hyacinth) showed the most drastic decrease in TDS from 538 mg/L to 210 mg/L. Treatment 4 (1200 ml of waste + 50 ml of ecoenzyme + water hyacinth) also showed a significant decrease in TDS from 538 mg/L to 245 mg/L. In addition, the addition of ecoenzyme helped stabilize the pH of the waste, tending to be close to neutral. The pH fluctuation in the treatment with ecoenzyme was more controlled compared to the phytoremediation treatment without ecoenzyme. The results of this study indicate that the combination of ecoenzyme and phytoremediation is an effective and potential method for processing laboratory waste from acid-base test practicums.